2020
DOI: 10.3390/healthcare9010012
|View full text |Cite
|
Sign up to set email alerts
|

Designing an IT Ecosystem for Pregnancy Care Management Based on Pervasive Technologies

Abstract: Pregnancy care is a topic of interest for both academia and practitioners. Novel pervasive technologies and applications, such as mobile technologies, wearables and IoT, open a wide corpus of possibilities for fostering pregnancy care management, and reducing risks and problems, improving communication among stakeholders and society development. This article introduces a model of a pregnancy care IT ecosystem based on the integration of various services in a semantically enriched e-health ecosystem. As proof o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The majority of mHealth apps reported in the selected studies were based on the so-called ecological momentary assessment approach [ 26 , 31 ], which allowed researchers to collect information about behaviours in real-time and in the real-world [ 44 , 45 ]. The use of data from social media, internet activities, Internet of Things (IoT) technologies, and specific surveys may also provide pertinent digital information to be considered [ 7 , 8 , 42 , 46 , 47 , 48 , 49 , 50 , 51 ]. Our scoping review also raised social and cultural issues, including concerns over data security and privacy, as well as fears about technology being intimately connected to the body.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of mHealth apps reported in the selected studies were based on the so-called ecological momentary assessment approach [ 26 , 31 ], which allowed researchers to collect information about behaviours in real-time and in the real-world [ 44 , 45 ]. The use of data from social media, internet activities, Internet of Things (IoT) technologies, and specific surveys may also provide pertinent digital information to be considered [ 7 , 8 , 42 , 46 , 47 , 48 , 49 , 50 , 51 ]. Our scoping review also raised social and cultural issues, including concerns over data security and privacy, as well as fears about technology being intimately connected to the body.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Pervasive technology such as mHealth and Internet of Things wearables present several opportunities for fostering pregnancy care management. 25 Nearly 75% of pregnant individuals reported downloading at least one mHealth app, and a majority of them indicated that they are likely to use them once per week. 26 , 27 Over 90% of women of reproductive age are smartphone users, including those on Medicaid.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, we felt it was essential to begin conducting rigorous studies aimed at designing (or co-designing with end-users), implementing, and subsequently evaluating telehealth interventions in this healthcare area [17][18][19]. Indeed, many available apps have been found to be unable to meet the needs and expectations of primary users and health professionals (i.e., secondary users) in terms of content validity [20,21], functionalities, and technical features [21,22]. Finally, most apps do not consider the continuum between pregnancy, birth, and postpartum and ultimately neglect the collective impact of the first 1000 days of life on women's and children's health [19,21,23].…”
Section: Introductionmentioning
confidence: 99%